2022
DOI: 10.5603/gp.a2021.0160
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of maternal and neonatal outcomes between planned and emergency cesarean deliveries in placenta previa patients without placenta accreata spectrum

Abstract: Objectives: This study aims to investigate whether a significant difference exists in maternal and fetal outcomes between planned cesarean delivery (PCD) compared to emergency cesarean delivery (ECD) in placenta previa (PP) patients without placenta accreata spectrum (PAS) in a tertiary referral hospital. Material and methods:This retrospective cohort study included 237 singleton pregnant women who were diagnosed with PP without PAS at the time of delivery. PP patients who were delivered at the scheduled time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 23 publications
0
23
1
Order By: Relevance
“…22 Gedik Özköse et al observed that 33.2% of patients with placenta previa underwent unscheduled delivery in the preterm period principally because of vaginal bleeding, labor pains, and fetal distress. 25 Erfani et al showed that 42.8% of pregnant patients with placenta previa (without placenta accreta spectrum) required emergent delivery because of premature labor contractions or vaginal bleeding. 26 Ruiter et al showed that of all patients with placenta previa who were planned for cesarean delivery after 37 weeks of gestation, 43% were unable to reach the scheduled delivery date, and the reason for 55% of these patients was severe hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…22 Gedik Özköse et al observed that 33.2% of patients with placenta previa underwent unscheduled delivery in the preterm period principally because of vaginal bleeding, labor pains, and fetal distress. 25 Erfani et al showed that 42.8% of pregnant patients with placenta previa (without placenta accreta spectrum) required emergent delivery because of premature labor contractions or vaginal bleeding. 26 Ruiter et al showed that of all patients with placenta previa who were planned for cesarean delivery after 37 weeks of gestation, 43% were unable to reach the scheduled delivery date, and the reason for 55% of these patients was severe hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also confirmed the significant relationship between PAS and the increasing number of CDs in cases with placenta previa (10,22,23). All women with placenta previa and PAS, regardless of history of previous CD, were at substantially increased risk of massive intraoperative hemorrhage, blood transfusion, additional surgical interventions such as cesarean hysterectomy, and maternal ICU admission (9,(23)(24)(25)(26). Our study also revealed a significant increase in the rates of placenta previa, placenta accreta, massive intraoperative hemorrhage, blood transfusion, uterine artery ligation, internal iliac artery ligation, cesarean hysterectomy, maternal ICU admission in cases undergoing multiple repeat CD compared with women having CDs after fewer previous CDs.…”
Section: Discussionmentioning
confidence: 57%
“…Thirteen studies compared the birth weights between the PCD and ECD groups. [16][17][18][19][20][21][22][23][24][25]27,28,33] However, one study [16] reported the medians of birth weight in 3 gestational ranges and therefore could not be pooled. In comparison to the ECD group, the pooled birth weight was significantly higher in the PCD group (SMD: 1.64; 95% CI: 1.00-2.27; P < .001; I 2 = 97%).…”
Section: Neonatal Birth Weightmentioning
confidence: 99%
“…Nine studies reported the means of gestational age at delivery in the PCD and ECD gro ups. [18][19][20][21][22]24,25,27,33] The overall pooled estimate for gestational age was significantly higher in the PCD group compared to the ECD group (SMD: 2.20; 95% CI: 1.25-3.15; P < .001; I 2 = 98%). This finding was also seen in the subgroups of women with PP alone (SMD: 1.29; 95% CI: 1.02-1.56; P < .001; I 2 = 22%) and PAS patients with or without coexistent PP (SMD: 2.51; 95% CI: 1.21-3.81; P < .001; I 2 = 98%) (Fig.…”
Section: Quantitative Analysesmentioning
confidence: 99%
See 1 more Smart Citation